Widening Geographical Disparities in Cardiovascular Disease Mortality in the United States, 1969-2011 - Gopal K. Singh, PhD; Romuladus E. Azuine, DrPH, RN; Mohammad Siahpush, PhD; Shanita D. Williams, PhD, MP (Global Health and Education Projects, Inc., 2015)
Objectives: This study examined trends in geographical disparities in cardiovascular-disease (CVD) mortality in the United States between 1969 and 2011. Methods: National vital statistics data and the National Longitudinal Mortality Study were used to estimate regional, state, and county-level disparities in CVD mortality over time. Log-linear, weighted least squares, and Cox regression were used to analyze mortality trends and differentials. Results: During 1969-2011, CVD mortality rates declined fastest in New England and Mid-Atlantic regions and slowest in the Southeast and Southwestern regions. In 1969, the mortality rate was 9% higher in the Southeast than in New England, but the differential increased to 48% in 2011. In 2011, Southeastern states, Mississippi and Alabama, had the highest CVD mortality rates, nearly twice the rates for Minnesota and Hawaii. Controlling for individual-level covariates reduced state differentials. State- and county-level differentials in CVD mortality rates widened over time as geographical disparity in CVD mortality increased by 50% between 1969 and 2011. Area deprivation, smoking, obesity, physical inactivity, diabetes prevalence, urbanization, lack of health insurance, and lower access to primary medical care were all significant predictors of county-level CVD mortality rates and accounted for 52.7% of the county variance. Conclusions and Global Health Implications: Although CVD mortality has declined for all geographical areas in the United States, geographical disparity has widened over time as certain regions and states, particularly those in the South, have lagged behind in mortality reduction. Geographical disparities in CVD mortality reflect inequalities in socioeconomic conditions and behavioral risk factors. With the global CVD burden on the rise, monitoring geographical disparities, particularly in low- and middle-income countries, could indicate the extent to which reductions in CVD mortality are achievable and may help identify effective policy strategies for CVD prevention and control.